2015
DOI: 10.1111/2041-210x.12324
|View full text |Cite
|
Sign up to set email alerts
|

Towards the identification of the loci of adaptive evolution

Abstract: 1. Establishing the genetic and molecular basis underlying adaptive traits is one of the major goals of evolutionary geneticists in order to understand the connection between genotype and phenotype and elucidate the mechanisms of evolutionary change. Despite considerable effort to address this question, there remain relatively few systems in which the genes shaping adaptations have been identified.2. Here, we review the experimental tools that have been applied to document the molecular basis underlying evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 282 publications
(477 reference statements)
1
113
0
Order By: Relevance
“…Of course, this is unless the biological characteristics (for example size, behaviour, generation time) prevent the applicability of this experiment. Common gardens could possibly even replace the field work required to obtain tissue samples for genotyping: as we mentioned, it would still allow for population genomics approaches, while guaranteeing independent validation through the study of phenotypes (Pardo-Diaz et al, 2014;Rellstab et al, 2015), hence saving the cost of another genotyping campaign. As emphasised by Lepais and Bacles (2014), deciphering the genetic basis of local adaptation will only be accomplished by combining all the information yielded by dense marker panels, careful experiments and in situ sampling and observations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, this is unless the biological characteristics (for example size, behaviour, generation time) prevent the applicability of this experiment. Common gardens could possibly even replace the field work required to obtain tissue samples for genotyping: as we mentioned, it would still allow for population genomics approaches, while guaranteeing independent validation through the study of phenotypes (Pardo-Diaz et al, 2014;Rellstab et al, 2015), hence saving the cost of another genotyping campaign. As emphasised by Lepais and Bacles (2014), deciphering the genetic basis of local adaptation will only be accomplished by combining all the information yielded by dense marker panels, careful experiments and in situ sampling and observations.…”
Section: Resultsmentioning
confidence: 99%
“…If a strong adaptive signal is detected both using both using genome scan methods (that is, using genotypic and possibly environmental data) and the phenotypic data from a common garden experiment, that will constitute two independent piece of evidence favouring the hypothesis of local adaptation (Holderegger et al, 2008). As stated above, genome scan results need to be validated anyhow (Pardo-Diaz et al, 2014;Rellstab et al, 2015), and performing a common garden experiment is an elegant way to do so. We suggested that, whenever possible, combining genome scan approaches with common garden experiments is an efficient approach to the study of local adaptation.…”
Section: What Is the Use Of Common Garden Experiments In The Genomic Era?mentioning
confidence: 99%
See 1 more Smart Citation
“…Field experimentation, linkage and association mapping, forward and reverse genetics, candidate gene approaches, functional molecular genetics and modelling are also crucial approaches for understanding the genetic basis of local adaptation (Kawecki & Ebert 2004;Hereford 2009;Anderson et al 2011;Savolainen et al 2013;Pardo-Diaz et al 2015).…”
Section: )mentioning
confidence: 99%
“…We examine whether ligand-coding genes are preferential targets for the generation of morphological evolution. In addition, we confront existing data to predictions that the corresponding allelic variation should be (1) potentially adaptive (Barrett and Hoekstra 2011;Pardo-Diaz et al 2015), (2) replicated over various phylogenetic levels (Gompel and Prud'homme 2009;Kopp 2009;Martin and Orgogozo 2013), and (3) cis-regulatory rather than coding (Prud'homme et al 2007;Carroll 2008;Stern and Orgogozo 2008;Liao et al 2010). …”
mentioning
confidence: 99%